Activation of ADAM17 by IL-15 Limits Human NK Cell Proliferation - Mishra, Hemant K.; Dixon, Kate J.; Pore, Nabendu; Felices, Martin; Miller, Jeffrey S.; Walcheck, Bruce (Frontiers in Immunology, 2021)
Natural killer (NK) cells are innate cytotoxic lymphocytes that can recognize assorted determinants on tumor cells and rapidly kill these cells. Due to their anti-tumor effector functions and potential for allogeneic use, various NK cell platforms are being examined for adoptive cell therapies. However, their limited in vivo persistence is a current challenge. Cytokine-mediated activation of these cells is under extensive investigation and interleukin-15 (IL-15) is a particular focus since it drives their activation and proliferation. IL-15 efficacy though is limited in part by its induction of regulatory checkpoints. A disintegrin and metalloproteinase-17 (ADAM17) is broadly expressed by leukocytes, including NK cells, and it plays a central role in cleaving cell surface receptors, a process that regulates cell activation and cell-cell interactions. We report that ADAM17 blockade with a monoclonal antibody markedly increased human NK cell proliferation by IL-15 both in vitro and in a xenograft mouse model. Blocking ADAM17 resulted in a significant increase in surface levels of the homing receptor CD62L on proliferating NK cells. We show that NK cell proliferation in vivo by IL-15 and the augmentation of this process upon blocking ADAM17 are dependent on CD62L. Hence, our findings reveal for the first time that ADAM17 activation in NK cells by IL-15 limits their proliferation, presumably functioning as a feedback system, and that its substrate CD62L has a key role in this process in vivo. ADAM17 blockade in combination with IL-15 may provide a new approach to improve NK cell persistence and function in cancer patients.